Identifying related commits from software repositories. (2015) - Hammad, Mustafa
Source code modifications are saved in software repositories as individual and independent commits. A highlevel programming task is usually applied by related or similar code changes activities. This paper presents an approach to automatically identify related and similar source code modifications from software repositories. Discovering related commits helps maintainers to understand and trace the implementation of a specific programming task. Furthermore, identifying commits of a programming task leads to simplify code fixing and debugging activities. The identification is based on discovering relations among commits from software repositories. A relation is exposed based on the textual similarity between commits. Therefore, commits relationships lead to categorise commits into disjoint groups. Each generated group would represent related or similar code modifications activities. A group can be a set of maintenance tasks related to a specific feature in the system. A case study on an open source project is presented to investigate the proposed approach.